Enhanced third-harmonic generation by manipulating the twist angle of bilayer graphene - Ha, Seongju; Park, Nam Hun; Kim, Hyeonkyeong; Shin, Jiseon; Choi, Jungseok; Park, Sungmin; Moon, Ji Yun; Chae, Kwanbyung; Jung, Jeil; Lee, Jae Hyun; Yoo, Youngdong; Park, Ji Yong; et al. (Light: Science and Applications, 2021)
Twisted bilayer graphene (tBLG) has received substantial attention in various research fields due to its unconventional physical properties originating from Moiré superlattices. The electronic band structure in tBLG modified by interlayer interactions enables the emergence of low-energy van Hove singularities in the density of states, allowing the observation of intriguing features such as increased optical conductivity and photocurrent at visible or near-infrared wavelengths. Here, we show that the third-order optical nonlinearity can be considerably modified depending on the stacking angle in tBLG. The third-harmonic generation (THG) efficiency is found to significantly increase when the energy gap at the van Hove singularity matches the three-photon resonance of incident light. Further study on electrically tuneable optical nonlinearity reveals that the gate-controlled THG enhancement varies with the twist angle in tBLG, resulting in a THG enhanced up to 60 times compared to neutral monolayer graphene. Our results prove that the twist angle opens up a new way to control and increase the optical nonlinearity of tBLG, suggesting rotation-induced tuneable nonlinear optics in stacked two-dimensional material systems.
Keywords: Electronic band structure; Interlayer interactions; Near-infrared wavelength; Optical nonlinearity; Third-order optical nonlinearities; Three-photon resonances; Two-dimensional materials; Van Hove singularities